Correlation of tangible quality parameters of vegetable-based transformer fluids - Adango Miadonye; Mumuni Amadu; James Stephens; Thomas O'Keefe (Heliyon, 2023)
Due to the inherent environmental footprint of petroleum derived transformer fluids, the power industry is gradually exploring the potential of vegetable oils as alternatives. The impetus comes mostly from vegetable oils renewability and their inherent biodegradability.However, the major drawback in the use of vegetable oils as dielectric fluids is their lower oxidative stability and higher kinematic viscosity compared to mineral oils. The results obtained clearly demonstrate the correlation between spectroscopic data induction time, kinematic viscosity, acid value, and peroxide value. Quantitatively, the absorption frequencies of functional groups in vegetable oil transformer fluids that can be correlated to the mentioned quality parameters show noticeable changes with aging/oxidative degradation. The study also demonstrates the utility of integrating spectroscopic data to understand trends in induction time and kinematic viscosity of oil samples heated under transformer service conditions.